Dissecting the PPP Puzzle: The Unconventional Roles of Nominal Exchange Rate and Price Adjustment - Yin-Wong Cheung; Kon S. Lai; Michael Bergman (Center for Economic Studies and ifo Institute (CESifo), 2003)
The conventional view, as expounded by sticky-price models, is that price adjustment determines the PPP reversion rate. This study examines the mechanism by which PPP deviations are corrected. Nominal exchange rate adjustment, not price adjustment, is shown to be the key engine governing the speed of PPP convergence. Moreover, nominal exchange rates are found to converge much more slowly than prices. With the reversion being driven primarily by nominal exchange rates, real exchange rates also revert at a slower rate than prices, as identified by the PPP puzzle (Rogoff, 1996).
Keywords: 330